Comparing Perspectives of Canadian Men Diagnosed With Prostate Cancer and Health Care Professionals About Active Surveillance. (December 2020) - Fitch, Margaret; Ouellet, Veronique; Pang, Kittie; Chevalier, Simone; Drachenberg, Darrel E; Finelli, Antonio; Lattouf, Jean-Baptiste; Loiselle, Carmen; So, Alan; Sutcliffe, Simon; Tanguay, Simon; Saad, Fred; et al.
Active surveillance (AS) has gained acceptance as a primary management approach for patients diagnosed with low-risk prostate cancer (PC). In this qualitative study, we compared perspectives between patients and health care professionals (HCP) to identify what may contribute to patient–provider discordance, influence patient decision-making, and interfere with the uptake of AS. We performed a systematic comparison of perspectives about AS reported from focus groups with men eligible for AS (7 groups, N = 52) and HCP (5 groups, N = 48) who engaged in conversations about AS with patient. We used conventional content analysis to scrutinize separately focus group transcripts and reached a consensus on similar or divergent viewpoints between them. Patients and clinicians agreed that AS was appropriate for low grade PC and understood the low-risk nature of the disease. They shared the perspective that disease status was a critical factor to pursue or discontinue AS. However, men expressed a greater emphasis on quality of life in their decisions related to AS. Patients and clinicians differed in their perspectives on the clarity, availability, and volume of information needed and offered; clinicians acknowledged variations between HCP when presenting AS, while patients were often compelled to seek additional information beyond what was provided by physicians and experienced difficulty in finding or interpreting information applicable to their situation. A greater understanding of discordant perspectives about AS between patients and HCP can help improve patient engagement and education, inform development of knowledge-based tools or aids for decision-making, and identify areas that require standardization across the clinical practice.